A Study on Redox Potential of Phytochemicals and their Impact on DNA - Singh Nitika; Kumar Gupta Vivek; K. Doharey Pawan; Srivastava Neeharika; Kumar Abhishek; Sharma Bechan (Journal of DNA And RNA Research, 2020)
The phytochemicals are endowed with antioxidant activities because of the presence of plentiful polyphenols and many other phytochemicals. However, some recent reports have suggested that phytochemicals from certain plant species exhibit DNA damaging properties mainly due to presence of alkaloids. In the present study, pBR322, Salmonella typhi DNA, insect DNA and human DNA were treated with hexanolic extract of Argemone mexicana and Thevesia peruviana leaves to assess their DNA damaging abilities. Another set of experiments was carried out using the methanolic extracts of Citrus lemon leaves to assess their DNA protecting abilities from damage of DNA by extracts of A. mexicana and T. peruviana at 150000 ppm for all DNAs used. The results indicated that the leaves extract of A. mexicanaand T. peruviana demonstrated significant DNA damaging potential at higher concentrations. In contrast, the extracts from C. limonat 15000 ppm showed maximum DNA protective properties for all DNAs used.
Keywords: DNA damage